스마트폰 기반 학생들의 주관적 웰빙과 충동성 분석 - 임소영 (The Graduate School, Ajou University, 2020)
As the use of mobile and wearable devices has become more common and sensor technology has developed, data collection for various activities of people has become possible. In particular, as various services throughout everyday life are provided through smartphones, it is possible to understand smartphone users' lifestyles. Accordingly, the analysis of smartphone-based physical and mental health and cognitive functions and the research to help people improve their physical and mental health through computing technology are being actively conducted. In addition, various discussions are being held in the field of psychology to utilize smartphone data that reflect people's activities and characteristics. In particular, it is said that by applying big data to psychological research, people's cognitive processes and behaviors can be explored, and data-based predictions can be applied to psychological areas. In this study, smartphone data was collected from Ajou University students (28), and smartphone data with self-reporting data related to mental health from KAIST students (80) were collected to analyze students' mental health and cognitive functions. Case Study 1 established a model for exploring and predicting mental health through data collected from KAIST students, and Case Study 2 sought to apply smartphone data to the psychological field by establishing a model for discovering and managing students' impulsive behavior in smartphone data from Ajou University and KAIST students.
학위논문(석사)--아주대학교 일반대학원 :컴퓨터공학과,2020. 8
Keywords: 긍정컴퓨팅; 디지털 표현형; 스마트폰; 주관적 웰빙; 충동성